A (re)municipalization trend among energy utilities: Truth or myth? - Astrid Cullmann; Maria Nieswand; Stefan Seifert; Caroline Stiel (DIW Economic Bulletin, 2016)
In the 1990s, a number of municipalities started privatizing their energy utilities; in recent years, there has been an intensive debate about whether a paradigm shift has taken place since then. Cities and municipalities have considered putting the energy, water, gas and heat supply back into the hands of public companies; Berlin and Hamburg are two prominent examples. But is there really an overarching trend toward (re)municipalization? According to the present study, which evaluates newly available microdata from official statistics, there is no evidence of a comprehensive (re)municipalization. The increase in public enterprises appears to have more to do with general restructuring in the energy sector, and has in fact been less pronounced than has growth in the private sector.
Keywords: L32; L22; L98; 330; public utilities; local government; energy